Superomedial pedicle skin-reducing mastectomy in ptotic and large-sized breasts with two-stage reconstruction through transaxillary video-assisted technique: An effective surgical and anesthetic approach - Di Monta, G.; Marone, U.; Avino, F.; Esposito, E.; Cepparulo, V.; Morra, E.; Saponara, R.; Bifulco, F.; Cuomo, A.; Cascella, M.; Mori, S. (Frontiers in Surgery, 2023)
Introduction Skin-reducing mastectomy has been applied to several surgical techniques in which subcutaneous mastectomy is associated with various types of skin reduction, with preservation of a lower dermal flap to reinforce the inferior lateral seat of an implant. The aim of the study is to present a case series of patients with pendulous/ptotic and/or large-sized breasts treated for breast cancer at the Breast Surgery Unit of Istituto Nazionale Tumori IRCCS Fondazione “G. Pascale”, Naples, Italy, with the superomedial pedicle skin-reducing mastectomy technique, two-stage reconstruction, and transaxillary video-assisted technique, when a postoperative radiotherapy was indicated. We verified its effectiveness by discussing its results, especially in patients who are candidates for postmastectomy radiotherapy. Materials and methods A single-center retrospective study was performed between January 2020 and March 2021 on a prospectively filled database of conservative mastectomies. Of the 64 patients who underwent nipple/skin-sparing mastectomies in the mentioned period, 17 (mean age 46 years, range 30–62 years) were treated with superomedial pedicle skin-reducing mastectomy, with two-stage breast reconstruction through transaxillary video-assisted replacement expander with definitive prosthesis and contralateral symmetrization, selected for postmastectomy radiotherapy. Results We had only three minor complications. No flap necrosis, no infections, no breast seromas, and no reconstructive failures were observed. During follow-up of the patients treated with video-assisted reconstruction, there were no cases of infection, hematoma, implant rupture, or suture dehiscence in the reconstructed breast. Discussion Skin-reducing mastectomy with superomedial pedicle is a safe and reliable procedure to treat breast cancer in selected patients, i.e., those with pendulous/ptotic and or large-sized breasts. Particularly, in patients who undergo postmastectomy radiotherapy, the two-stage reconstruction with video-assisted transaxillary endoscopic approach can find its main indication, using incisions positioned far from the mammary region, offering numerous advantages.